2017
DOI: 10.1016/j.jeurceramsoc.2016.12.044
|View full text |Cite
|
Sign up to set email alerts
|

The effect of graphene nanoplatelets on the thermal and electrical properties of aluminum nitride ceramics

Abstract: The thermal conductivity () of AlN (2.9 wt. % of Y 2 O 3 ) is studied as a function of the addition of multilayer graphene (from 0 to 10 vol. %). The  values of these composites, fabricated by spark plasma sintering (SPS), are independently analyzed for the two characteristic directions defined by the GNPs orientation within the ceramic matrix; that is to say, perpendicular and parallel to the SPS pressing axis. Conversely to other ceramic/graphene systems, AlN composites experience a reduction of  with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 32 publications
(57 reference statements)
2
34
1
Order By: Relevance
“…The obtained critical GNP percolation volume fraction (V h,c = 0.0118) is within the lowest reported up to now for graphene/ceramic composites (Figure 5b), which show critical volume filler contents for percolation ranging between 0.38 and 2.0 % for rGO containing composites [7][8][9] and from 2.0 up to 9.0 for composites with thicker GNP [8,10,30,31]. Therefore, this limit appears obviously related to the distribution and dispersion of the fillers.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 85%
“…The obtained critical GNP percolation volume fraction (V h,c = 0.0118) is within the lowest reported up to now for graphene/ceramic composites (Figure 5b), which show critical volume filler contents for percolation ranging between 0.38 and 2.0 % for rGO containing composites [7][8][9] and from 2.0 up to 9.0 for composites with thicker GNP [8,10,30,31]. Therefore, this limit appears obviously related to the distribution and dispersion of the fillers.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 85%
“…K  increases above 30 % were also stated for B 4 C/GNP[44,81] composites(Figure 16b), while irrelevant rises and even decreases on K  were reported for Al 2 O 3 /GNP[75] and AlN/GNP[70,83] composites, respectively. This decrease in thermal conduction for the inplane direction has been explained in a recent work by the existence of matrix/graphene interfacial thermal resistances[70]. FromFigure 16c, increasing K  /K || values with the GNP content (within the range of ~2.0-4.0) are reported for ceramic…”
mentioning
confidence: 61%
“…In a recent paper by some of the present authors[70], the thermal behaviour of AlN/GNP materials in both directions has been conveniently reproduced by introducing in the effective media thermal conductivity model a contact thermal conductance (h c ) of  3 x 10 8 W m -2 K -1 at the AlN/GNP interface. This value agrees with calculations done for the…”
mentioning
confidence: 99%
“…have excellent thermal, electrical, and mechanical properties. Extensive research has shown that nanocarbon can enhance many properties of ceramics, for example, the mechanical, frictional [6][7][8][9], electrical [10][11][12][13], and thermal properties [14][15][16]. As a result, nanocarbon is regarded as an ideal reinforcing phase in ceramic matrix materials.…”
Section: Introductionmentioning
confidence: 99%